Theoretical Principles of Realization Social-Pedagogical Patronage in the Family - .Andreichuk, Lesya (Pedagogical Discourse, 2012)
The problem of realization social-pedagogical patronage under the family conditions in the context of theoretical principles generalization is revealed in the article. Main definitions of the problem, principles and functions of social-pedagogical patronage are reflected, social patronage and social-pedagogical patronage are correlated, peculiarities of work of family social pedagogue are revealed.